Engine testing : electrical, hybrid, IC engine and power storage testing and test facilities. - Martyr, Anthony; Rogers, David (David R.) (Butterworth-Heinemann, 2021)
Engine Testing: Electrical, Hybrid, IC Engine and Power Storage Testing and Test Facilities, Fifth Edition covers the requirements of test facilities dealing with e-vehicle systems and different configurations and operations. Chapters dealing with the rigging and operation of Units Under Test (UUT) are updated to include electric motor-based systems, test cell services and thermo-dynamics. Control module and system testing using advanced, in-the-Loop (XiL) methods are described, including powertrain component integrated simulation and testing. All other chapters dealing with test cell design, installation, safety and use together with the cell support systems in IC engine testing are updated to reflect current developments and research.